2018
DOI: 10.1017/mor.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship between Justice and Extra-Role Behavior: The Role of State Ownership

Abstract: State ownership is an important phenomenon in the world economy, especially in transition economies. Previous research has focused on how state ownership influences organizational performance, but few studies have been conducted on how state ownership influences employees. I propose that different ownership structures trigger different relational models among employees who pay attention to organizational justice consistent with their model to guide their extra-role behavior. Specifically, state-owned organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 119 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Organizational justice and employee innovative behavior. OJ is likely a motivational factor of EIB because of its vital impact on employee attitudes and behaviors (Pan et al, 2018), including those that are discretionarily performed (Akram et al, 2016;Chen, 2018;Momeni et al, 2014). The influence of OJ on EIB has been widely emphasized from both the theoretical and empirical standpoints.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational justice and employee innovative behavior. OJ is likely a motivational factor of EIB because of its vital impact on employee attitudes and behaviors (Pan et al, 2018), including those that are discretionarily performed (Akram et al, 2016;Chen, 2018;Momeni et al, 2014). The influence of OJ on EIB has been widely emphasized from both the theoretical and empirical standpoints.…”
Section: Hypothesismentioning
confidence: 99%
“…In this context, as OJ is suggested to play a major role in employee attitudes and behaviors (Pan et al, 2018; Silva, 2015), including extra-role behaviors (Chen, 2018), it is likely to influence EIB in the organizational context. Justice and other motivation theories assume that employees tend to make efforts to improve their organizations when they judge them as fair (Moon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The pressure of maintaining harmony might be particularly resonant for senior executives in SOEs as group solidarity, interpersonal harmony, and mutual sharing are more pronounced in this environment due to the socialistic ideology (X. Chen, 2018;Michael & János, 1985). In a qualitative study of the reform of performance appraisal in state banks, Gu and Nolan's (2017) research participants revealed that they had a level of high concern of losing mianzi (or face) due to poor appraisal outcomes (F. Gu & Nolan, 2017).…”
Section: Harmony As An Important Goalmentioning
confidence: 99%
“…In a similar vein, frequent organisational changes resulting from economic reforms, regulatory changes, and increasing competition appear to challenge the traditional value of interpersonal harmony and group solidarity in the Chinese workplace (X. Chen, 2018; C. Q. Lu et al, 2009).…”
Section: Overview Of the Researchmentioning
confidence: 99%
“…This tendency is further strengthened by socialistic values such as collectivism, group solidarity, and communal sharing preserved in the public sector (X. Chen, 2018;Michael & János, 1985). From this perspective, the overlap between social and organisational values can promote the need for harmony maintenance in the workplace.…”
Section: Debating the Universality Of Harmony-maintenance Challengesmentioning
confidence: 99%